Application of circular technical services in a living lab in Ghent - Lefevre, Lode; Kayaçetin, Cihan; Breesch, Hilde; Smeyers, Lieven; Versele, Alexis (CLIMA 2022 conference, 2022)
The construction industry in the EU possesses great potential for mitigating environmental impacts because of its large share in resource use and waste production. The Circular Economy Action Plan of the EU stimulates the sector to adopt more circular principles and bio-based material use. The European Interreg 2 Seas project “Circular Bio-Based Construction Industry” (CBCI) is in line with these European ambitions researching technical, economical, legal and, social aspects. In the course of the project, a prototype for a terraced single-family house called the living lab (LL) Ghent is developed and constructed in close collaboration with multiple stakeholders of the construction sector. The building implements and tests the research outputs in a real-life setting. During the development of LL, the circularity of building components was taken into account by utilizing the layers of Brand approach. Among those layers are structure, skin, technical services and, space plan. On the one hand, each layer has its specificity (e.g. life duration). For example, for technical services and space plan, components are subject to upgrades and/or replacement more often than those in other layers. The retention and reuse of valuable materials and components need to be anticipated. This calls for circular strategies and solutions corresponding to each layer. On the other hand, the layers are interdependent and integrated in terms of energy performance and spatiality. This interconnectedness compromises the efficacy of the applied circular strategies. Despite the need for such circular strategies, existing assessment tools seldom focus on technical services due to a lack of appropriate design methods and increased investment costs of components suitable for reuse. This paper documents the translation of existing European assessment tools as method and related design strategies for layers of structure, skin and space plan to the layer of technical services. The selected design strategy was an iterative process ensured by a design & build procurement and the solution for the integration of technical services was determined as a plug-in unit which is part of a modular CLT technical core. It is expected that the technical unit will continue its lifetime beyond the lifetime of LL Ghent.